Biaya Produksi dan Daya Saing Relatif Usahatani Lada Hitam dan Putih Indonesia - Ekwasita Rini Pribadi; Agus Wahyudi (Buletin Penelitian Tanaman Rempah dan Obat, 2021)
Indonesia is one of the major pepper (Piper nigrum L.) producer countries in the world. The main pepper products are distinguished into black and white pepper. Each region has a tradition to produce each of the products and influencing cultivation practices and cost structure. This research was aimed to analyze the cost of productions of black and white pepper and their relative competitiveness to the pepper price at the farm level with conventional and improved cultivation practices. The survey methods were used to obtain the primary data from respondents selected with the snowball sampling method. Lampung and Bangka Belitung Islands were chosen to represent the black and white peppers of smallholders, respectively. The result showed that the farms with conventional cultivation practices did not have sustainable relative competitiveness, indicating higher production costs than the lowest prices received in the long term. On the other hand, relative competitiveness was relatively better in farms that implemented improved cultivation practices. Therefore, to achieve sustainable relative competitiveness, pepper farms should apply improved cultivation practices. The relative competitiveness of white pepper was better than black pepper because the productivity of white pepper was higher even though the production cost was also a little bit higher than black pepper.